The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12951-023-02223-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in melittin-based nanoparticles for antitumor treatment: from mechanisms to targeted delivery strategies

Xiang Yu,
Siyu Jia,
Shi Yu
et al.

Abstract: As a naturally occurring cytolytic peptide, melittin (MLT) not only exhibits a potent direct tumor cell-killing effect but also possesses various immunomodulatory functions. MLT shows minimal chances for developing resistance and has been recognized as a promising broad-spectrum antitumor drug because of this unique dual mechanism of action. However, MLT still displays obvious toxic side effects during treatment, such as nonspecific cytolytic activity, hemolytic toxicity, coagulation disorders, and allergic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…There have been attempts to alter the sequence of MEL or ne-tune the conformation of MEL [23]. Studies have also been conducted on the delivery of MEL using smart nanocarrier strategies to achieve passive or active targeting for the treatment of recurrent and refractory malignancies [24]. The tumor-homing peptide RGD recognizes global proteins present on the surface of cancer cells and speci cally targets the vascular region of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to alter the sequence of MEL or ne-tune the conformation of MEL [23]. Studies have also been conducted on the delivery of MEL using smart nanocarrier strategies to achieve passive or active targeting for the treatment of recurrent and refractory malignancies [24]. The tumor-homing peptide RGD recognizes global proteins present on the surface of cancer cells and speci cally targets the vascular region of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The cationic nature of melittin may qualify it to play a crucial role in the disruption of cancer cell membranes through electrostatic attraction between the negatively charged membrane components of cancer cells and the positive charges of the alkaline peptides ( Adler-Nissen, 1979 ). Because of its excellent immunomodulatory effects, antitumor potency, and its ability to overcome tumor drug resistance, melittin, therefore, represents a promising agent for cancer treatment ( Yu et al, 2023 ). Moreover, a previous study showed that melittin treatment induces apoptosis in human gastric cancer (SGC-7901) cells via modulating mitochondria pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nanofibers play an important role in tumor therapy, especially in overcoming the problem of tumor drug resistance. 25 , 170 Tumor drug resistance refers to the phenomenon in which tumor cells become resistant to chemotherapeutic drugs and is one of the main causes of tumor treatment failure. NPs as drug carriers can deliver chemotherapeutic drugs precisely to the tumor site, improving the therapeutic effect of the drug and reducing side effects.…”
Section: Overview Of Npsmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 , 22 , 23 In the field of oncology, NPs have been extensively studied as drug carriers to overcome the problem of drug resistance faced by conventional chemotherapeutic agents. 24 , 25 NPs as drug carriers have the following advantages. First, NPs can be used efficiently for drug delivery, encapsulating chemotherapeutic agents and ensuring high drug concentrations are distributed to tumor sites to improve therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%